Spittoon Philosophers or Radical Revolutionaries? The Canadian Administration of the Industrial Workers of the World, 1932-35 - Beaulieu, Michel (Ontario History)

(untitled) (The Ontario Historical Society, 2013)
Historians contend that the heyday of the Industrial Workers of the World (IWW or Wobblies) in the U.S. and Canada ended when it was suppressed by the authorities in the First World War because of the “foreigners” within its ranks. However, the IWW went underground and re-emerged briefly in the late 1920s and 1930s as a force in lumber and mining unions in both countries. Little is known about its organization during this period, particularly the operations of the Canadian Administration established in 1932. This article explores the activities of Canadian Wobblies and their attempts to form a Canadian Administration between 1931 and 1935 in Port Arthur, Ontario. It establishes that the Canadian leadership increasingly separated itself from an ineffectual American leadership and attempted to establish uniquely “Canadian” polices.